The Failure of Monetary Policy to Prevent the Depression of 1929-32 - Currie, Lauchlin (Journal of Political Economy, 1934)
It is generally accepted that the internal and external situation in 1929 posed contradictory demands with respect to monetary policy. According to Currie this is an erroneous point of view. Both the international and national situations of that time demanded the withdLdwa1of monetary restrictions. This, along with the maintenance of relatively stable prices and level of economic activity, could have partially prevented the consequences of a world recession. The argument for maintaining the monetary restriction was the rise in speculation. Nevertheless, it is fl0t clear chat speculation harmed productive investment or much less that it was an important cause of the recession In fact, and contrary to general opinion that maintained that the excesses of the "boom" were to blame for the gravity of the depression, the author shows that the Le was neither a ·'boom" nor inflation during the 1920s. This was, rather, a time of stability. The deficiencies of monetary policy, the concludes, were greatly responsible far originating the crisis. By concentrating primarily on stopping Speculation, the analysis of the level of economic activity as a whole was neglected. Far from preventing the recession, this served to set it off.